Multimodal Analgesia Protocol after Head and Neck Surgery: Effect on Opioid Use and Pain Control. (September 2019) - Du, Eugenie; Farzal, Zainab; Stephenson, Elizabeth; Tanner, April; Adams, Katherine; Farquhar, Douglas; Weissler, Mark; Patel, Samip; Blumberg, Jeffrey; Jowza, Maryam; Hackman, Trevor; Zanation, Adam
Objective: To assess the effect that implementation of a multimodal analgesic plan has on opioid requirements and pain control in head and neck (H&N) surgery patients. Study Design: Prospective cohort. Setting: Tertiary academic hospital. Subjects and Methods: An institutional review board (IRB)–approved quality improvement initiative was undertaken to implement a multimodal analgesic protocol for all admitted H&N surgery patients starting November 2017. Postprotocol data from January to May 2018 were compared to preprotocol data from May to October 2017. Data were obtained from the electronic health records as well as through preoperative and postoperative surveys. Average pain scores and opioid use in morphine milligram equivalents (MMEs) before and after protocol implementation were compared. Results: In total, 139 postprotocol patients were compared to 89 preprotocol patients. The adjusted MMEs in the first 24 hours after surgery decreased significantly from 93.7 mg to 58.6 mg ( P = .026) with protocol implementation. When averaged over the length of stay (MME/hospital day), the change was no longer statistically significant (57.9 vs 46.8 mg, P = .211). The average pain score immediately after surgery and on day of discharge did not change with protocol implementation. Conclusion: Implementation of a multimodal analgesia plan reduced opioid use immediately after surgery but not over the course of hospitalization without any change in reported pain scores. This study shows that multimodal opioid-sparing analgesia after H&N surgery is feasible. Future studies are needed further refine the optimal analgesic strategy for H&N patients and assess the long-term efficacy, safety, and cost of such regimens.